1996
DOI: 10.1111/j.1439-0442.1996.tb00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Topographical Mapping of Gastric Helicobacter‐like Organisms and Their Association with Histological Changes in Apparently Healthy Dogs and Cats

Abstract: s-aryThe occurrence and topographical mapping of the gastric Helcobacter-like organisms (GHLOs) and their association with histological changes were studied in apparently healthy dogs and cats. Multiple samples were collected for histological examination from the fundus, corpus and antmm of the stomach of 10 dogs and 10 cats. Fundus and corpus were also sampled for transmission electron microscopy (three dogs, six cats), and for culture (eight dogs, six cats). In all dogs, GHLOs were detected in the fundus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 21 publications
9
89
1
3
Order By: Relevance
“…Urease testing and cytology were less sensitive and did not give any information about the species identity. Helicobacters were found less frequently in the antrum than in other regions of the stomach, a result which is in agreement with former studies (19,20).…”
Section: Discussionsupporting
confidence: 82%
“…Urease testing and cytology were less sensitive and did not give any information about the species identity. Helicobacters were found less frequently in the antrum than in other regions of the stomach, a result which is in agreement with former studies (19,20).…”
Section: Discussionsupporting
confidence: 82%
“…and experimental infection with H. felis. 36,79,80,91 The reasons for this difference in colonization density are unclear. Differences in the microenvironmental conditions from the different sites of the gastric mucosa may be a factor.…”
Section: Discussionmentioning
confidence: 99%
“…in the present study is similar to that reported in cats, captive exotic carnivores, and small felids naturally infected with Helicobacter. 32,36,39,48 Although the differences in histopathological findings may be related to the species of Helicobacter, factors such as the size of tissue sample examined, the age of the cat, and the presence or absence of clinical signs also must be considered. Differences in the size of the tissue samples taken from H. pylori-and H. felis-infected cats (6 mm) versus those taken from cats infected with H. heilmannii and unclassified Helicobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of Helicobacter organisms in dogs' stomach confirmed by different studies [2,4,7,13,[17][18][19] . In spite of confirmation of H. pylori as a main cause SHABESTARI ASL, AMANIZAD, NEJAD PARTOVI, JALILI, MOHAMMAD NEZHAD, SOROUSH, BARZEGARI, BABAZADEH of human chronic gastritis and gastric malignancy, the exact role of gastric helicobacters in dogs has not been established yet [2,7,8] .…”
Section: Discussionmentioning
confidence: 75%
“…[1,8,11,12] , but the exact role of these fastidious bacteria is not confirmed yet [2,7,8] . Until now, different Helicobacter species have been isolated from canine stomachs [2,4,[13][14][15] ; but it is not known whether these species are representative of all canine gastric helicobacters or which of them are most common [8,14] . Different studies have reported dissimilar ranges of contamination [3][4][5][6]16] and some of these reports were showed high prevalence (over 90%) of contaminations [17][18][19] .…”
Section: öZetmentioning
confidence: 99%